Nanoscale Optical Logic Circuits by Single-Step FRET - Jinya Inoue; Takahiro Nishimura; Yusuke Ogura; Jun Tanida (IEEE Photonics Journal, 2020)
We propose a method for implementing nanoscale optical logic circuits via single-step Förster resonance energy transfer (FRET). Use of single-step FRET enabled circuits with simple design and high expandability. Two kinds of FRET gates, a YES gate and a NOT gate, were used to modulate fluorescence output signals based on light inputs. Various logic circuits could be implemented by connecting FRET gates on a DNA structure. The experimental results demonstrated that FRET gates for two kinds of input lights were constructed, and that logic circuits executing the AND and OR operations produced fluorescence signals as outputs.